2014
DOI: 10.3390/su6041643
|View full text |Cite
|
Sign up to set email alerts
|

Co-Producing Sustainability: Involving Parents and Civil Society in the Governance of School Meal Services. A Case Study from Pisa, Italy

Abstract: There is a rising awareness of the power of the public sector in enhancing sustainable consumption and production practices, in particular related to food procurement and its social, ethical, economical and environmental implications. School meal services have a high resonance in the debate on collective catering services because of the implications on the education to sustainable dietary habits and the orientation of the production system. This contribution focuses on the reciprocal relationship between profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 42 publications
3
84
0
5
Order By: Relevance
“…As Soule and Olzak (2004) conclude, although many researchers make assumptions about the causes of political change, few studies have examined these processes empirically. If we look at the recent studies about CSOs and social innovation (Jing and Gong, 2012; Galli et al, 2014;Gonzales et al, 2014;Franz, Tausz and Thiel, 2015;Seyfang and Longhurst, 2016), the conclusions are in the same sense. These studies, as shown by Andion et al, 2017, emphasize the functional and economic dimensions of social innovation, which is described as a way for CSOs to contribute to government and public policy.…”
Section: Civil Society Organizations and Social Innovation How And Tmentioning
confidence: 77%
See 2 more Smart Citations
“…As Soule and Olzak (2004) conclude, although many researchers make assumptions about the causes of political change, few studies have examined these processes empirically. If we look at the recent studies about CSOs and social innovation (Jing and Gong, 2012; Galli et al, 2014;Gonzales et al, 2014;Franz, Tausz and Thiel, 2015;Seyfang and Longhurst, 2016), the conclusions are in the same sense. These studies, as shown by Andion et al, 2017, emphasize the functional and economic dimensions of social innovation, which is described as a way for CSOs to contribute to government and public policy.…”
Section: Civil Society Organizations and Social Innovation How And Tmentioning
confidence: 77%
“…The purpose of this study is to understand the social innovation processes promoted by civil society organizations (CSOs) in public arenas, a theme that is not widely explored in the literature as discussed by Rana et al (2014). This paper concentrates on the political dimension of social innovation driven by CSOs and not just on their functional, economic and/or technical dimensions, which have been increasingly considered in recent scholarly works (Galli et al, 2014;Gonzales et al, 2014;Franz, Tausz and Thiel, 2015;Seyfang and Longhurst, 2016)…”
Section: Conclusiones Prácticas Y Valor Originalmentioning
confidence: 99%
See 1 more Smart Citation
“…Since conventional thermal treatments such as combustion, gasification, and pyrolysis may not be used for energy generation from Municipal Solid Waste (MSW), Rice Waste (RW), Cow Dung (CD), etc., anaerobic digestion can be considered as the best option for energy generation from the above wastes, which are normally available in an educational institution. It is also reported that the food waste generated in schools can be effectively used for biogas generation, and it can be recycled through composting in order to produce useful end products [16][17][18]. Most of the previous studies focused on the constant loading rate of biowaste to predict biogas generation.…”
Section: Introductionmentioning
confidence: 99%
“…This turn was marked by a notion that individuals may be regarded as competent and rational actors/agents, and should more closely be involved in day-to-day politics, as they can reflect on their preferences during these open dialogues (Chambers 2003;Ganuza and Francés 2012). More recently, new public governance studies increasingly began highlighting the importance of citizen involvement in local decision-making processes to generate through social interactions suitable approaches to matters of public concern (Galli et al 2014;Head and Alford 2015;Lovan et al 2017). Previous studies indicated that citizen participation processes designed using deliberation-centric approaches could lead to more informed, involved, and educated citizens (Luskin et al 2002;Gutmann and Thompson 2009;Arendt 2010;Grönlund et al 2010).…”
Section: Introductionmentioning
confidence: 99%